Anti-BCMA CAR-T Cell Therapy in Relapsed/Refractory Multiple Myeloma Patients With Extramedullary Disease: A Single Center Analysis of Two Clinical Trials - Que, Yimei; Xu, Menglei; Xu, Yanjie; Almeida, Varlene Daniela Fernandes; Zhu, Li; Wang, Zhiqiong; Wang, Ying; Liu, Xian; Jiang, Lijun; Wang, Di; Li, Chunrui; Zhou, Jianfeng (Frontiers in Immunology, 2021)
Background: The prognosis of relapsed/refractory multiple myeloma (RRMM) patients with the extramedullary disease was significantly poor. Extramedullary multiple myeloma (EMM) patients gained limited benefits from traditional drugs. Anti-B cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T-cell therapy seems to be a promising approach to treat RRMM patients. However, very few clinical studies are designed for EMM. Our study aimed to compare and assess the safety, efficacy, and pharmacokinetics of anti-BCMA CAR-T cell therapy in EMM and non-EMM. Methods: The results from published anti-BCMA CAR-T clinical trials, in which raw data of EMM patients was available, were reviewed and summarized. Two trials conducted in our clinical centers were analyzed and presented with detailed data. Results: Between February 22, 2017, and September 26, 2019, a total of 61 subjects (EMM 25; non-EMM 36) received anti-BCMA CAR-T cell infusion. There were no statistical differences between EMM and non-EMM groups in adverse events (AEs), including cytokine release syndrome (CRS). The most common AEs of grade ≥ 3 in both groups were hematologic toxicities. There was no significant difference in the objective response rate (ORR) and ≥ complete remission (CR) rate between both groups. However, the ≥ CR rate of the EMM group was lower than the non-EMM group receiving the fully human anti-BCMA CAR-T cell therapy (p = 0.026). The median progression-free survival (PFS) for EMM and the non-EMM group was 121 days and 361 days, respectively (p = 0.001). The median overall survival (OS) for EMM and the non-EMM group was 248 days and 1024 days, respectively (p = 0.005). The Cmax and AUC0-28d for EMM group were lower than non-EMM group (Cmax, p = 0.016; AUC0-28d, p = 0.016). Extramedullary disease was an independent prognostic risk factor for PFS (hazard ratio, 2.576; 95% CI, 1.343 to 4.941; p = 0.004) and OS (hazard ratio, 2.312; 95% CI, 1.165 to 4.592; p = 0.017) in RRMM patients receiving anti-BCMA CAR-T cell therapy. Conclusions: Anti-BCMA CAR-T cell therapy is safe and effective for EMM. However, EMM patients had a shorter PFS and OS compared with non-EMM patients. Trial registration: http://www.chictr.org.cn: ChiCTR-OPC-16009113 and ChiCTR1800018137.